Broadband sound absorption by a nested doll metasurface using multi-slit synergetic resonance. (2nd October 2020) - Liu, Hongxing; Wu, Jiu Hui; Li, Bing; Lei, Yunzhong; Ma, Fuyin
Abstract: A sound-absorbing metasurface with a multi-slit synergetic resonant effect was studied that can achieve broadband sound absorption in a range betwen 500 Hz and 1150 Hz by using a nested doll supercell with a thickness of only 44.1 mm (the thickness being one sixteenth of the wavelength). The basic unit of the improved micro-slit absorber (IMSA), made by designing the slit of the micro-slit absorber as a type of step and locating it at the edge of the surface panel, is proposed for sound absorption at lower frequencies. The improved step slit can not only change the structure's impedance to match the medium of air at a lower frequency, but can also guide sound waves into the slit and increase the air velocity step by step, which results in a strong friction loss in the lower micro-slit. On this basis, a nested doll supercell with eight integrated parallel IMSAs was designed and tested, and was able to achieve sound absorption in a range between 500 Hz and 1150 Hz. In addition, the bandwidth was further broadened (to between 330 Hz and 1150 Hz) by adding four additional IMSAs to the previous supercell, while the surface area of the panel only increased by about 20%. This work highlighted the potentially extensive application of broadband noise reduction due to its depth, i.e. subwavelength thickness, and the relatively small surface area of the panel.